2017
DOI: 10.1021/acs.energyfuels.7b02746
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigation of the Effects of Zwitterionic Surface-Active Ionic Liquids on the Interfacial Tension of a Water/Crude Oil System and Their Application To Enhance Crude Oil Recovery

Abstract: Two zwitterionic surface-active ionic liquids (SAILs), 3-(1-hexadecyl-3-imidazolio) propanesulfonate (C16IPS) and 3-(1-hexadecyl-3-imidazolio) propanesulfonate β-naphthalenesulfonate (C16IPS-Nsa), were evaluated for their potential application in chemical enhanced oil recovery. It was found that the zwitterionic SAILs had a higher interfacial activity than the traditional SAILs. Interestingly, the C16IPS-Nsa molecule with the large hydrophobic group β-naphthalenesulfonate had a greater ability for reducing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Some of the researchers have also studied the effectiveness of dicatanionic, gemini-type, and zwitterionic based SAILs in reducing IFT between oil and water. ,,,, Zhou et al studied the effectiveness of a series of gemini imidazolium SAILs with a four-methylene spacer group (C n D, n = 8, 10, 12) in reducing the IFT between water and a model oil (toluene and n -decane, v : v = 1:1) . They found that under similar conditions gemini C n D molecules can more efficiently reduce the IFT as compared to single chain C n S molecules, n = 8, 10, 12.…”
Section: Screening Of Sails On the Basis Of Their Efficiency In Reduc...mentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the researchers have also studied the effectiveness of dicatanionic, gemini-type, and zwitterionic based SAILs in reducing IFT between oil and water. ,,,, Zhou et al studied the effectiveness of a series of gemini imidazolium SAILs with a four-methylene spacer group (C n D, n = 8, 10, 12) in reducing the IFT between water and a model oil (toluene and n -decane, v : v = 1:1) . They found that under similar conditions gemini C n D molecules can more efficiently reduce the IFT as compared to single chain C n S molecules, n = 8, 10, 12.…”
Section: Screening Of Sails On the Basis Of Their Efficiency In Reduc...mentioning
confidence: 99%
“…They found that [P 4 4 4 1 ]­[DS] reduces IFT more effectively as compared to the anionic surfactant, sodium dodecyl sulfate, having the same tail length . Jia et al evaluated potential application of two zwitterionic SAILs, 3-(1-hexadecyl-3-imidazolio) propanesulfonate (C 16 IPS) and 3-(1-hexadecyl-3-imidazolio) propanesulfonate β-naphthalenesulfonate (C 16 IPS-Nsa), in chemical enhanced oil recovery . They compared the interfacial activity of the two zwitterionic SAILs with two traditional SAILs, C 16 MPB ( N -hexadecyl- N -methylpyrrolidinium bromide) and C 16 mimBr (1-hexadecyl-3-methylimidazolium bromide), having the same cationic headgroup and alkyl chain and found that both of the zwitterionic SAILs displayed higher efficiency in reducing IFT between oil and water as compared to the traditional SAILs, C 16 MPBr and C 16 mimBr.…”
Section: Screening Of Sails On the Basis Of Their Efficiency In Reduc...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, research has been focusing mainly on the use of chemical additives. Various surfactants have been investigated for their ability to induce destabilization [11][12][13][14][15] , but the last years the focus has also shifted to using biosurfactants [16][17][18] and surface active ionic liquids [19][20][21] . However, the main issue remains that these chemical additives acquire additional steps to separate them from the water phase.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a promising and facile approach to fabricate desired surfactants via noncovalent interactions was proposed in supramolecular chemistry (Mali et al, ; Zhang and Wang, ). Based on the electrostatic attraction, we introduced some novel surfactant systems (anionic/cationic surfactants, Gemini‐like surfactants, and zwitterionic surface‐active ionic liquids) to chemical EOR, which showed the satisfactory ability to reduce the IFT at high salinity and temperature (Jia et al, , ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%